2011 IEEE/ASME International Conference on Advanced Intelligent Mechatronics (AIM) 2011
DOI: 10.1109/aim.2011.6027042
|View full text |Cite
|
Sign up to set email alerts
|

The design and characteristic research of a dual-mode inertia motor

Abstract: The design of a dual-mode inertia motor involves an actuator that can generate translational and rotational motion without connecting the actuators serially. Traditionally, translational or rotational actuators should be stacked serially to have multi-axis degrees-of-freedom. The experimental results of this study display performance characteristics such as linearity, resolution, velocity and the most excellent operating frequency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…It has been measured using different methods: making the slider move against a spring, the force is either determined from the deformation of the spring [61,74,75], or using a load cell connected to the spring [76,77]. Other authors make the slider move directly against a load cell [67,[78][79][80][81], or the force is exerted to a part connected to a load cell instead of a slider [82].…”
Section: Force Generationmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been measured using different methods: making the slider move against a spring, the force is either determined from the deformation of the spring [61,74,75], or using a load cell connected to the spring [76,77]. Other authors make the slider move directly against a load cell [67,[78][79][80][81], or the force is exerted to a part connected to a load cell instead of a slider [82].…”
Section: Force Generationmentioning
confidence: 99%
“…Recently, it has been shown that running the slider against a spring is a robust method of determining the force generation potential of an inertia motor, providing results independent of the spring stiffness as long it is sufficiently low ( [87] (pp. [73][74][75][76][77], in short form also [77] (p. 7)). This method is also suited for non-iterative numerical simulation [87] (pp.…”
Section: Force Generationmentioning
confidence: 99%
See 1 more Smart Citation
“…A piezoelectric inertia motor is a type of electric motor that transforms electrical energy into motion using the inverse piezoelectric effect (Uchino, 1997). Piezoelectric inertia motor has a simple construction and can be simply controlled using single driving signal (Cheng and Hung, 2011; Hunstig and Hemsel, 2010). Piezoelectric inertia motor consists of three main components: sliding rod, piezoelectric actuator, and slider.…”
Section: Introductionmentioning
confidence: 99%